POLICY STRATEGY OF RURAL AGRIBUSINESS BUSINESS DEVELOPMENT PROGRAM IN THE DEVELOPMENT OF AGRICULTURAL-BASED SHARIA MICROECONOMICS IN WEST SUMBAWA REGENCY - Ariani, Zaenafi (Journal of Sharia Economy and Islamic Tourism, 2020)
A common problem for farmers so far is not having good access to financing institutions, making it difficult to obtain credit or financing of agricultural businesses, such as people's business loans (KUR) from banks. That's why, the Directorate General of Infrastructure and Facilities and Agriculture (PSP) Ministry of Agriculture ( Kementan) rolled out the Rural Agribusiness Business Development Program (PUAP) until now. With the revitalization of agricultural financing is expected to be one of the efforts aimed at encouraging and guaranteeing the availability of financing / capital for farmers in the development of farming To support the success of agricultural development, the government through the Minister of Agriculture of the Republic of Indonesia provided Direct Assistance to the Rural Agribusiness Development Community (BLM-PUAP) which was rolled out to the Combined Farmer Groups (Gapoktan) in each village, with the hope that all villages in NTB Province, especially in West Sumbawa Regency can be accommodated.